Challenges and Opportunities in Strengthening ASEAN Space Technology Cooperation - Astri Rafikasari (IKAT: The Indonesian Journal of Southeast Asian Studies, 2020)
ASEAN is regional cooperation between countries in the Southeast Asia region to benefit its member states. Amidst much ongoing teamwork, regional space cooperation has not been optimized as it is still limited to the use of technology. By applying a qualitative method, this paper aims to describe the challenges and opportunities in strengthening the ASEAN Space Technology Cooperation. It may either hinder or even potentially frame a sustainable international relation that accommodates ASEAN member states to develop more possibilities to maximize the use of space technology. This literary study argues that ASEAN Space Technology Cooperation may become a robust bridge to transfer space technology, strengthen national, regional, and international security, enhance economic growth, and means of transferring knowledge or space education to its member states.